The density of collagen fiber in alveolus mandibular bone of rabbit after augmentation with powder demineralized bone matrix post incisivus extraction - Regina TC. Tandelilin; Abdul Salam M. Sofro; Al Supartinah Santoso; Marsetyawan HNE Soesatyo; Widya Asmara (Dental Journal (Majalah Kedokteran Gigi), 2006)
The bone defect due to tooth extraction contributes the most cases reported in the aspects of oral surgery. The defect can be preventively managed by adding powder bone matrix intended for augmentation which eventually induces the formation of new bones. This hard tissue wound healing is preceded by the presence of collagen fibers. The aim of this study was to determine the density of collagen fiber in the alveolus mandibular bone of rabbit which was augmented using powder demineralized bone matrix (DBM) post incisivus extraction. Twenty four male rabbits aged 2.5–3 months weighed 900–1,100 grams were randomly divided into two groups. The treated rabbits were augmented with DBM after the incisivus extraction on mandible. The mucosa was then sutured. On the other hand, the controlled rabbits received similar treatments with those of the treated rabbits except there was no augmentation of DBM. Decapitation of treated and controlled rabbits was made on day 5, 7, 10, and 14 days post surgery, each with three rabbits. Mandibles were cut, decalcified, and imbedded in paraffin block. The staining was done using Mallory. Significant differences in the density of collagen were noted on day 10 and 14 post surgery, indicating that powder demineralized bone matrix successfully induced the stimulation of collagen.